The Effect of Pressure, Rationalization, Religiosity on Academic Fraud Behavior - Evelyne Shafina; Mardi Mardi; Achmad Fauzi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This research aims to determine the effect of pressure, rationalization, religiosity towards academic fraud. The research used quantitative methods, data were collected with survey techniques and using a questionnaire (likert scale). The population were all accounting students in XI grades with totaling 108 people. Using a proportional random sampling technique with a total sample of 85 people. The data analysis technique used is the requirements analysis test, the regression equation test, and the hypothesis test. The results of this research indicate that there is a simultaneous significant effect of pressure, rationalization, religiosity towards academic fraud. Partially, pressure and rationalization have a positive and significant effect towards academic fraud, as well as a negative and significant effect of religiosity towards academic fraud. The test results of multiple correlation coefficient (R) of 0.775 have a close relationship and a determination coefficient of 58.5% indicates that pressure, rationalization, religiosity in influencing academic fraud. These findings indicate that the higher of pressure and rationalization, the higher of academic fraud and vice versa. Meanwhile, the lower of level religiosity, the higher level of academic fraud and vice versa. Keywords: pressure, rationalization, religiosity, academic fraud